Acknowledging Diversity: Need of Hour in Education - Yadav, Neha (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Diversity entails differences among individuals in terms of their religion, caste, language, region, culture, traditions, customs, etc. India being a pluralistic society these differences are evident amongst learners in classrooms as well. The need of the hour is to acknowledge this diversity amongst learners in our classrooms and appreciate the heterogeneous pool present in our classrooms. This would help to make the instruction specific to the individual needs of the students resulting in a boost to the educational outcomes of the students concerned